Comparison of Alternative Methods for Bioaccumulation Assessment: Scope and Limitations of In Vitro Depletion Assays with Rainbow Trout and Bioconcentration Tests in the Freshwater Amphipod Hyalella azteca. (9th July 2020) - Kosfeld, Verena; Fu, Qiuguo; Ebersbach, Ina; Esser, Dana; Schauerte, Anna; Bischof, Ina; Hollender, Juliane; Schlechtriem, Christian
Abstract: Bioaccumulation assessment predominantly relies on the bioconcentration factor (BCF) as the sole decisive metric. The test guideline 305 by the Organisation for Economic Co‐operation and Development (OECD) provides the standard procedure for deriving this in vivo fish BCF, which is not only expensive and labor‐intensive, but also requires many animals. Accordingly, there is a great need for and interest in alternative methods that can help to reduce, replace, and refine vertebrate tests, as described in the 3R principles. Two alternative approaches have been developed: the bioconcentration test with the freshwater amphipod Hyalella azteca and the OECD test guideline 319 which provides a method to determine experimentally derived in vitro metabolism rates that can then be incorporated into in silico prediction models for rainbow trout BCF calculation. In the present study both alternative methods were applied to 5 substances of different physicochemical characteristics. The results were compared with literature values of fish in vivo BCFs and additional BCFs obtained with the alternative methods, if available. Potential differences between the results of the test methods are discussed utilizing information such as in vivo metabolism rates. The currently available data set suggests that these 2 alternative methods pose promising alternatives to predict bioaccumulation in fish, although defined applicability domains have yet to be determined. Environ Toxicol Chem 2020;39:1813–1825. © 2020 The Authors. Environmental Toxicology and Chemistry published by Wiley Periodicals LLC on behalf of SETAC